Inflight Modifications of Content: Who are the Culprits? - Zhang, Chao; Huang, Cheng; Ross, Keith W.; Maltz, Dave; Li, Jin (LEET'11 Proceedings of the 4th USENIX conference on Large-scale exploits and emergent threats, Boston, MA, 2011)
When a user requests content from a cloud service provider, sometimes the content sent by the provider is modified inflight by third-party entities. To our knowledge, there is no comprehensive study that examines the extent and primary root causes of the content modification problem. We design a lightweight experiment and instrument a vast number of clients in the wild to make two additional DNS queries every day. We identify candidate rogue servers and develop a measurement methodology to determine, for each candidate rogue server, whether the server is performing inflight modifications or not. In total, we discover 349 servers as malicious, that is, as modifying content inflight, and more than 1.9% of all US clients are affected by these malicious servers. We investigate the root causes of the problem. We identify 9 ISPs, whose clients are predominately affected. We find that the root cause is not sophisticated transparent in-network services, but instead local DNS servers in the problematic ISPs.